Linguistic changes in the 1768 second edition of Matija Kastelec’s Mesec božje ljubezni [The Month of God’s Love] from the collection Nebeški cilj [Heavenly Goal] (1684) - Orel, Irena (Slavia Centralis, 2021)
Based on a comparison of Matija Kastelec’s original text Mesec božje ljubezni [The Month of God’s Love] from Nebeški cilj [Heavenly Goal] (1684) and an adapted independent edition from 1768, the article sheds light on the linguistic changes (orthography and spelling, phonology, morphology, syntax and lexicology), which correspond to a shift from Kastelec’s traditional Lower Carniolan Baroque literary norm to the younger Upper Carniolan literary norm at the beginning of the national renaissance in the second half of the 18th century, comparable to the norm in Marko Pohlin’s Carniolan Grammar (1768). The starting point of the linguistic comparison is Martina Orožen’s work, in which she outlines the guidelines for language development and recognizes that Kastelec’s language displays continuity with the Protestant tradition and the Stična manuscript from the 15th century.
Keywords: The History of the Slovene Literary Language; Linguistic Changes; Slovene Baroque; Beginning of the National Renaissance